2017
DOI: 10.18632/oncotarget.19856
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review and meta-analysis comparing zoledronic acid administered at 12-week and 4-week intervals in patients with bone metastasis

Abstract: Zoledronic acid is used to treat patients with bone metastasis, but the optimal dosing interval remains controversial. We therefore performed a systematic review and meta-analysis to compare the efficacy and safety of a 12-week interval of zoledronic acid with the standard 4-week interval. Three randomized controlled trials comprising 2650 patients were analyzed. Using a random-effects model, pooled risk ratios (RRs) and 95% confidence intervals (CIs) were calculated. No differences in the occurrence of skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Among breast cancer patients, ZA therapy every 12 week—rather than every 4 week—has been proposed and might be considered an acceptable treatment schedule. Indeed, no difference in terms of SREs occurrence has been observed, while incidence of ONJ and kidney dysfunction resulted lower in the 12-week population, even if statistical significance was not reached [ 111 ] . In DTC population, randomized trial data to clarify this issue have not yet been published.…”
Section: Managementmentioning
confidence: 99%
“…Among breast cancer patients, ZA therapy every 12 week—rather than every 4 week—has been proposed and might be considered an acceptable treatment schedule. Indeed, no difference in terms of SREs occurrence has been observed, while incidence of ONJ and kidney dysfunction resulted lower in the 12-week population, even if statistical significance was not reached [ 111 ] . In DTC population, randomized trial data to clarify this issue have not yet been published.…”
Section: Managementmentioning
confidence: 99%
“…Therefore, longer follow-up updates are warranted to investigate if the SRE events will change in the two compared schedules. Despite these evident limits, the present study, as suggested by the previous meta-analysis by Ling Cao (Cao et al, 2017), suggests that compared with the standard 4-week intervals, the administration of zoledronic acid at 12-week intervals do not significantly increase SREs and time to SREs and may reduce the occurrence of jaw osteonecrosis, hypocalcaemia and kidney dysfunction. Additionally, for the first time our results assessed the equivalence of the two different schedules of zoledronic acid in term of SMR.…”
Section: Discussionmentioning
confidence: 46%
“…Conventional nanoparticle-based formulations follow a passive targeting mechanism i.e., the enhanced permeation and retention effect may not be suitable due to the lack of leaky vasculature at the metastases bone sites. , Zoledronic acid is a third-generation bisphosphonate drug molecule widely used clinically to minimize pain and skeletal related events in patients with bone metastases . This molecule comprises bisphosphonate, which has strong binding potential with hydroxyapatite of the bone, thus it is a bone-directing molecule. , Upon reaching the bone, ZA forms strong bonds with calcium, which are stable in bone for about a year. Therefore, purpose of the current study was to develop a structurally well-defined nanoparticle system for effective targeting of bone and treat bone metastasis.…”
Section: Introductionmentioning
confidence: 99%